Application of Green Accounting and Implementation of Circular Economy in Inorganic Waste Processing - Ni Ketut Suarma DEWI; Pande Kadek Nova Dwi MAHARANI; Ni Putu Ayu Ratna ANGGRENI; Ni Luh Lestari PIRAYANTI (Loka: Journal Of Environmental Sciences, 2024)
Purpose:This study aims to analyze the application of green accounting and the implementation of a circular economy business model in inorganic waste processing in Tegal Tugu Village. Green accounting, which focuses on recording and managing environmental impacts, is expected to help measure and manage natural resources more sustainably. Meanwhile, the circular economy offers an approach to recycling and reusing inorganic waste to create economic value and reduce waste.Methodology:The research method used is a case study with a qualitative approach, involving interviews with stakeholders in the village and analysis of documents related to waste management.Findings:The results of the study indicate that the application of green accounting in inorganic waste processing can provide economic and environmental benefits. However, challenges related to public awareness and infrastructure availability still need to be overcome.Implication:In addition, the implementation of a circular economy business model has contributed to waste reduction and the creation of new economic opportunities at the village level. This study suggests increasing collaboration between the government, community, and private sector to strengthen the implementation of both concepts in order to create sustainability in waste management in the village.